A Model of Collateral - Yu Awaya; Hiroki Fukai; Makoto Watanabe (Tinbergen Institute, 2017)
This paper presents a simple equilibrium model in which collateralized credit emerges endogenously. Just like in repos, individuals cannot commit to the use of collateral as a guarantee of repayment, and both lenders and borrowers have incentives to renege. Our theory provides a micro-foundation to justify the borrowing constraints that are widely used in the existing macroeconomic models. We provide an explanation to the question of why assets are often used as collateral, rather than simply as a means of payment, why there is a tradeoff in assets between return and liquidity, and what kinds of assets are useful as collateral.
Keywords: C73; 330; collateral; search; medium of exchange; voluntary separable repeated game